PSXII-6 Supplementation of Angus crossbred steers with avian-derived polyclonal antibody preparations against the ruminal methanogen Methanobrevibacter ruminantium M1 does not alter in vivo methane emissions. (30th November 2020) - Garcia-Ascolani, Mariana E; Schulmeister, Tessa M; Tarnonsky, Federico; Podversich, Federico; da Silva, Gleise Medeiros; Martinez, Juan Vargas; Ruiz-Moreno, Martin; Batista Dubeux, Jose Carlos; Hackmann, Timothy J; DiLorenzo, Nicolas
Abstract: An experiment was conducted to evaluate the effect of supplementing twenty Angus crossbred steers with avian-derived polyclonal antibody preparations (PAP) against the ruminal methanogen Methanobrevibacter ruminantium M1 on in vivo methane production, using the sulfur hexafluoride (SF6 ) tracer technique (Johnson et al., 1994). Steers were fed chopped bermudagrass hay (BGH) ad libitum and 0.7 kg d -1 of corn gluten feed. The experiment followed a change-over design. Treatments were 1) supplementation of 3 mL d -1 of PAP against M. ruminantium M1 (PAP-M1), and 2) supplementation of 3 mL d -1 of a non-immunized egg product (CON). Individual BGH intake was recorded using an electronic radio-frequency monitoring system (GrowSafe System Ltd., Airdrie, Alberta, Canada). There was a 14-d adaptation period to the feeding regime, with no PAP supplementation, followed by an 18-d treatment period. Steers were dosed with brass permeation tubes with a known release rate of SF6 on d 7 of treatment period. Enteric methane emissions were sampled from d 13 to 18 of the treatment period, into N-rinsed pre-evacuated U-shaped polyvinyl chloride canisters (2 L) through a capillary tube. Methane emissions were averaged per animal within period. Data were analyzed as a change-over design using a model with fixed effects of order, period, and treatment and random effect of steer within order. Dry matter intake (DMI) was not different (P = 0.44) between treatments. Methane emissions, expressed as grams per day (P = 0.86), as grams per kilogram of DMI (P = 0.78), or in terms of methane emission factors (Ym, P = 0.78) were not different between PAP-M1 and CON treatments. Supplementation of steers with PAP against M. ruminantium M1 did not decrease enteric methane emissions. Based on preliminary ex situ trials, evaluation of different doses and combinations of PAP against other methanogenic species warrant further investigation.